Exploring the Relationship Between Board Characteristics and Environmental Disclosure: Empirical Evidence for European Firms - Jamel Chouaibi; Emna Miladi; Nizar Elouni (Journal of Accounting and Management Information Systems (JAMIS), 2022)
Research Question - Does the effect of selected board characteristics is contingent on the level of environmental disclosure by European firms. Motivation - Sustainable development is based on a vision where the protection of the environment, social progress and economic efficiency are indispensable. Idea - This research aims to investigate the effect of selected board characteristics on the level of environmental disclosure by European firms. Data - This study used a sample of 220 European companies under the context of a new dataset, namely, DataStream ASSET database. Corporate environmental disclosure index (CEDI) is developed to measure the level of environmental information. Tools - This index is calculated based on the CEDI-related items provided by DataStream ASSET4. Findings - The multiple linear regression analyses were used to verify the effect of the board of directors' characteristics on the level of environmental disclosure. The results indicate that the board size and board independence have a statistically significant and positive impact on the level of environmental disclosure. Contribution - The findings have important implications for different policymakers; It helps inform regulatory regulators of the importance of good corporate governance to lay the foundation for comprehensive environmental disclosure by establishing valuable relationships with different stakeholders.
Keywords: M41; M16; O16; 650; Environmental disclosure; board of directors; corporate governance; European companies